Nutrient density and affordability of aquatic foods in the FAO uFISH database assessed using Nutrient Rich Food (NRF) indices - Johnsson, Emma; Harris, Cristen; Drewnowski, Adam (Frontiers in Nutrition, 2025)
BackgroundFish and shellfish are valuable sources of high-quality protein, vitamins, and minerals. Their nutrient density and price vary by species.ObjectivesThis study aimed to determine nutrient density and nutrient affordability per unit cost of fish and shellfish in the FAO/INFOODS uFISH database.MethodsTwo versions of the Nutrient Rich Food (NRF) index were constructed. The NRF was based on a positive subscore, NRn, and a negative subscore, LIM. The NR6 subscore was the sum of percent daily values (%DV) for 6 priority micronutrients widely identified to be lacking in low and middle-income countries, including iron, zinc, calcium, vitamin A, vitamin B12, and folate. The NR9 subscore, specifically tailored to include micronutrients relevant to fish and shellfish, was the sum of %DV for protein, calcium, iron, potassium, magnesium, selenium, vitamin A, vitamin D, and omega-3 fatty acids. The LIM subscore was based on saturated fat and sodium. In both cases NRFn.2=NRn−LIM, with %DV calculated per 100 g and capped at 100%. Food prices, obtained from GlobeFish, were converted to the cost per 100 g protein. A new Affordability Index for Aquatic Foods was calculated as nutrient density per unit cost.ResultsThe NRF6.2 score identified mollusks, and especially bivalves, as the best aquatic source of priority micronutrients. The NRF9.2 revealed small pelagic fish as the most nutrient rich, followed by bivalves. Mackerel, tilapia, squid, and mussels provided the most protein, NRF6.2 nutrients, and NRF9.2 nutrients per penny.ConclusionFish and shellfish are an affordable source of protein, omega-3 fatty acids, and priority micronutrients. However, there were species differences in cost and nutrient density, with mackerel, mussels, tilapia, octopus, and squid scoring the highest for nutrient density at an affordable cost.